The Impact of Open-Ended Based Learnıng Modıfıed by Realıstıc Mathematıc Educatıon on Computatıonal Thınkıng Skılls - Maryam Aunurrahim; Yurniwati Yurniwati; Faisal Madani (Elementary Teacher Education Program, Majalengka University, 2024)
This research was based on the problem of students' computational thinking skills that are still low, especially in elementary school mathematics subjects in term of students' mathematics anxiety. One solution is to use a learning method to improve computational thinking skills: Problem Based Learning (PBL) modified with the Open-Ended Problem (OEP) and Realistic Mathematic Education (RME) approaches to produce the Open-Ended Based Learning Modified by Realistic Mathematic Education (OEBL-RME) method. The purpose of this study is to determine the impact of the OEBL-RME method on computational thinking skills in terms of mathematics anxiety in elementary school students. This research used quasi-experimental method of post-test only control group design using a design treatment by level 2x2. Data were collected using computational thinking skills tests and math anxiety questionnaires and analyzed with the 2-way ANAVA test using SPSS 27. The sample used was 108 grade V elementary school students consisting of 54 students in the experimental class and 54 students in the control class. The results showed that there is an impact of OEBL-RME method on students' computational thinking skills in learning mathematics. In addition, it is proven that there is an interaction between learning methods and mathematical anxiety towards computational thinking skills.